(untitled) (المجلة الدولية للبحوث العلمية, 2026)
The study aims to identify the primary causes of failures in thermal, waterproofing, and acoustic insulations in buildings and to propose management techniques to inform technical solutions. Several analytical methods were employed to achieve this objective, including statistical sampling for data collection. The text also included analyses of insulation materials, affinity diagrams for action to classify and organize failure causes, and a multi-criteria decision analysis to select the most appropriate solutions. The leading causes of failures identified across the test cases were poor surface preparation of adhesion joints, inappropriate material selection, incorrect installation sequence, inadequate joint treatment, exposure of insulation materials to the external environment before finishing, and lack of coordination among insulation systems. Flaws in insulation give rise to thermal bridges, moisture infiltration, reduced thermal efficiency and damage. Engineering solutions were proposed to enhance insulation based on the research conclusion. Building with an integrated thermal envelope concept, selection of insulation material, storage installation, and execution quality control. The originality of this research lays in a framework that integrates project management techniques for decision-making with construction insulation analysis to improve reliability, reduce failure risk, and enhance the sustainability of building performance.